Parental Care, Parental Overprotection and Delinquency among Adolescents - Hina Ali Lone (Pakistan Journal of Mental Health, 2025)
The aim of this study was to investigate the relationship between parental care, parental overprotection, and delinquency among adolescents. A sample of 200 adolescents was selected with an age range of 16 to 18 years from Gujranwala, Pakistan. The Parental Bonding Questionnaire and Self-Report Delinquency Scale were used in the study. The data was analysed by SPSS version 27, by using descriptive and inferential statistics that were computed. Results revealed that parental care was significantly negatively related to delinquency, whereas parental overprotection was significantly positively related to delinquency among adolescents. On investigating gender differences, it was found that male adolescents show a higher level of delinquency as compared to female adolescents.